Penerapan Remodelling Pembelajaran PAI pada Anak dengan Gangguan Pemusatan Perhatian dan Hiperaktif di SD Muhammadiyah - Ismah, Mahiroh; Anshori, Isa (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study aims to describe the process of remodeling learning materials for children with special needs with attention deficit hyperactivity disorder (ADHD), and how it is implemented in the classroom. This research uses qualitative methods, namely research by approaching or tracing to explore and understand a problem. The results of this study are that children with ADHD have different characteristics from their peers, so they require different methods and approaches in the teaching and learning process. The curriculum used for students with special needs must pay attention to the needs and academic potential of the child. This research is expected to be a reference for educators to be able to maximize the potential of children with special needs in their class.